2018
DOI: 10.1007/s00262-018-2213-1
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD8+ T-cell repertoires reveal the biological characteristics of tumors and clinical responses to chemotherapy in breast cancer patients

Abstract: Although functional studies of clonally expanded CD8 T-cell populations are clearly required, our results suggest that the circulating CD8 T-cell repertoire reflects the characteristics of the tumor-associated biomolecules released into the blood and correlates with the clinical responses of the patients to chemotherapy which might assist in making treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…In this study, we performed TCRβ repertoire HTS of the PBMC of MN patients in pre-and post-therapy stages, as well as of PBMC of healthy controls, to investigate the relevance of T-cell immunity and the clinical characteristics of MN. Many studies indicated aberration in the usage of the TCRβ V gene and J gene in autoimmune diseases and cancers (15)(16)(17)(18)(19)(20). In this study, we found a similar situation in MN patients.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In this study, we performed TCRβ repertoire HTS of the PBMC of MN patients in pre-and post-therapy stages, as well as of PBMC of healthy controls, to investigate the relevance of T-cell immunity and the clinical characteristics of MN. Many studies indicated aberration in the usage of the TCRβ V gene and J gene in autoimmune diseases and cancers (15)(16)(17)(18)(19)(20). In this study, we found a similar situation in MN patients.…”
Section: Discussionsupporting
confidence: 81%
“…In theory, MN is an immune-related disease. If the treatments were effective, the immune status of the body will be different form the pre-treatment, and the TCRβ repertoire will also change significantly; this has been reported in various types of immunemediated diseases (19,34,35). We therefore calculated the similarity of the TCRβ repertoire between pre-and post-therapy in each patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive body of work has indicated the value of the recovery of TCR recombination reads from tumor specimen WXS files for correlative studies, as detailed in the Introduction . It is also clear that TCR recombinations representing T cells reactive against cancer antigens can be identified in the blood . Recent work has indicated that blood‐exome‐derived recombination reads identify V and J usage, HLA allele combinations that strongly correlate with cervical cancer outcomes .…”
Section: Resultsmentioning
confidence: 99%
“…It is also clear that TCR recombinations representing T cells reactive against cancer antigens can be identified in the blood. 6,26 Recent work has indicated that blood-exome-derived recombination reads identify V and J usage, HLA allele combinations that strongly correlate with cervical cancer outcomes. 27 This latter result is consistent with the presumed systemic nature of human papillomavirus infection, which in turn, for a subset of infected persons, leads to cervical cancer.…”
Section: Recovery Of Tcr Recombination Reads From Blood Wxs Files Repmentioning
confidence: 99%